2022
DOI: 10.1021/acs.macromol.2c00311
|View full text |Cite
|
Sign up to set email alerts
|

Glass Transition Dynamics of Poly(phenylmethylsiloxane) Confined within Alumina Nanopores with Different Atomic Layer Deposition (ALD) Coatings

Abstract: Dielectric spectroscopy (DS) and differential scanning calorimetry (DSC) were employed to study the effect of changes in the surface conditions on the segmental dynamics of poly­(phenyl­methylsiloxane) confined in alumina nanopores (AAO). The inner surface of the pores was modified by using the atomic layer deposition technique. Coated membranes include 5 nm thick layers of hafnium oxide, titanium oxide, and silicon oxide, exhibiting different wetting properties. Modification of the surface conditions dramatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 110 publications
2
3
0
Order By: Relevance
“…Interestingly, the combination of dielectric and calorimetric data revealed that the temperature at which the change in τ α occurs agrees with the calorimetric glass transition temperature assigned to the vitrification of the interfacial molecules (adsorbed on the pore walls, T g,interfacial ) . According to this hypothesi,s below T g,interfacial , immobilized adsorbed molecules generate pseudoisochoric conditions, where free volume barely varies, resulting in a change in the temperature dependence of structural relaxation times that mimics τ α ( T ) evolution at constant volume. , Finally, one should also mention recent studies that clearly showed that roughness-induced variation in the mobility of adsorbed molecules strongly affects the overall dynamics of polymer films, which agrees with the results of molecular dynamics simulation studies. Nevertheless, surprisingly, the chemical modification of the inner pore walls (leading to the change in the strength of interfacial interactions) does not influence T g,interfacial . This data increases doubt about the vitrification of the interfacial layer being responsible for a change in the molecular dynamics of confined materials.…”
supporting
confidence: 76%
See 4 more Smart Citations
“…Interestingly, the combination of dielectric and calorimetric data revealed that the temperature at which the change in τ α occurs agrees with the calorimetric glass transition temperature assigned to the vitrification of the interfacial molecules (adsorbed on the pore walls, T g,interfacial ) . According to this hypothesi,s below T g,interfacial , immobilized adsorbed molecules generate pseudoisochoric conditions, where free volume barely varies, resulting in a change in the temperature dependence of structural relaxation times that mimics τ α ( T ) evolution at constant volume. , Finally, one should also mention recent studies that clearly showed that roughness-induced variation in the mobility of adsorbed molecules strongly affects the overall dynamics of polymer films, which agrees with the results of molecular dynamics simulation studies. Nevertheless, surprisingly, the chemical modification of the inner pore walls (leading to the change in the strength of interfacial interactions) does not influence T g,interfacial . This data increases doubt about the vitrification of the interfacial layer being responsible for a change in the molecular dynamics of confined materials.…”
supporting
confidence: 76%
“…This indicates that the behavior of the highly polar liquid infiltrated into porous membranes is not governed by wettability but rather by other factors, probably the density packing and the lower extent of guest–host interactions. Importantly, similar effects have been reported for poly­(methylphenylsiloxane) (PMPS) within AAO templates …”
supporting
confidence: 75%
See 3 more Smart Citations